(untitled) (The Pakistan Development Review, 2016)
Serious financial crisis in Pakistan energy sector, mainly due to poor governance, rising fuel prices and rampant corruption, led to the decision of corporatisation of Water and Power Development Authority (WAPDA) in 1992. However, this decision has been highly debated in the context of its socio economic benefits as the energy crises continues unabated. This study, by using semi-structured interview from energy experts in the power sector, attempts to find the factors that withheld the positive effects of this decision. The objective is to provide useful input to frame future energy policy to overcome critical energy crises in Pakistan. The study concludes that the decision of corporatisation of WAPDA was a forced decision without proper homework recommended by the International Monetary Fund (IMF) which worked as an obstacle to achieve required targets in context of energy crises. However, expert opinion shows that unbundling of WAPDA if managed adequately in line with the ground realities would help bring in the competition in market and support the neoliberal theory which calls for deregulation of businesses and privatisation of publicly owned assets, thus minimising the state intervention. Therefore, the only choice for the government is to move forward with the reforms to frame efficient and effective power policy. Chile, with successful power reforms, is the example quoted by the experts to be followed by Pakistan to overcome load shedding and black outs. JEL Classification: H7 Keywords: Energy, Pakistan Energy Sector, WAPDA, Neoclassical Theory, Corporatisation, Privatisation, Restructuring, Governance